Annual Report on Exchange Arrangements and Exchange Restrictions 1997. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 1997)
This 1997 Annual Report on Exchange Arrangements and Exchange Restrictions provides a detailed description of the exchange arrangements and exchange restrictions of individual member countries, including Hong Kong, China, for which the United Kingdom had accepted the IMF Articles of Agreement, and Aruba and the Netherlands Antilles, for which the Kingdom of the Netherlands has accepted the IMF Articles of Agreement. In general, the description relates to the exchange and trade systems as of the end of 1996, but in appropriate cases, reference is made to significant developments that took place in early 1997.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet